Adaptive Hybrid Archival Management and Educational Personnel Performance: Evidence from a Pesantren-Based Madrasah in Indonesia - Fanita Ayuwandira; Ismatul Izzah; Nur Fitri Amalia (Al-Qalam Institue, 2026)
Archival management is essential to governance because records support accountability, institutional memory, and service quality. However, pesantren-based madrasahs often face fragmented procedures, limited storage, and uneven digital capacity. This study aims to analyze archival management and its contribution to personnel performance at Madrasah. A qualitative descriptive design was employed using purposive sampling. Data were collected through interviews, observation, and document analysis, then analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that archival planning is adaptive and based on needs. Records are classified by type and year, but written SOPs are unavailable. Archival implementation combines manual and digital systems, creating a hybrid model. Collaborative task distribution supports administrative continuity. Periodic supervision improves document order, although evaluation remains informal. Organized archives accelerate retrieval, improve information accuracy, and support BOS reporting, examinations, accreditation, and services. Nevertheless, limited storage, incomplete digitization, and uneven digital competence reduce efficiency. The study implies that hybrid archival governance can sustain performance under resource constraints. Strengthening SOPs, staff competence, digital integration, and evaluation is essential for accountable and sustainable madrasah administration.